PENGARUH LINGKUNGAN BELAJAR TERHADAP MOTIVASI BELAJAR SISWA KELAS VIII B SMP AL-RIFA’IE GONDANGLEGI - Shalsa Alawiyah Nuha; Ika Ratih Sulistiani; Lia nur Atiqoh Bela Dina (VICRATINA, 2020)
In the learning process much needed motivation to learn. Student learning motivation is not only influenced by how children actively learn and understand the lesson, but also the condition of a supportive learning environment that will affect student learning motivation.This study uses a quantitative approach. The population in this study were students of class VIII B Al-Rifa’ie Gondanglegi junior high school, amounting to 28 students. Data collection techniques using a questionnaire. Data analysis techniques using validity, reliability, normality and linearity tests. Hypothesis testing uses a simple regression test.The results showed that the learning environment of VIII B students of Al-Rifa’ie Gondanglegi Middle School was classified in the high category, with a percentage of 54% or as many as 15 students from 28 students with an average of 63.4643. The learning motivation of eighth grade students of Al-Rifa’ Gondanglegi Middle School is classified in the high category, with a percentage of 53% or as many as 15 students out of 28 students with an average of 137.25. Based on the results of this study indicate the influence of student learning environment on the motivation of eighth grade students of Al-Rifa’ie Gondanglegi Middle School. Significant value of 0,000, which means less than the probability of 0.05. So it can be concluded that there is an influence of the learning environment (X) on learning motivation (Y).The results of this study are expected to be information and input for teachers and schools in order to create conducive environmental conditions for students